Exposure to active and passive smoking among Greek pregnant women. Issue 1 (December 2016) - Vivilaki, Victoria; Diamanti, Athina; Tzeli, Maria; Patelarou, Evridiki; Bick, Debra; Papadakis, Sophia; Lykeridou, Katerina; Katsaounou, Paraskevi
Abstract Background Active smoking and exposure to passive smoke are responsible for numerous adverse pregnancy outcomes for women and their infants. The aim of this study was to explore the perceptions, attitudes, patterns of personal tobacco use and exposure to environmental smoke among a sample of pregnant women in Greece. Method A cross sectional survey was undertaken of 300 women identified from the perinatal care records of the Maternity Departments of two hospitals in Athens between February 2013 and May 2013. Data on active and passive maternal smoking status in the first, second, and third trimesters of pregnancy, fetal and neonatal tobacco related complications, exposure to environmental tobacco smoke during pregnancy, quit attempts, behaviors towards avoiding passive smoking and beliefs towards smoking cessation during pregnancy were collected using self-administered questionnaires on the 3rd postnatal day. Women also completed the Edinburgh Postnatal Depression Scale (EPDS). Results Of 300 women recruited to the study 48 % reported tobacco use during the first trimester of pregnancy. Amongst participants who were tobacco users, 83.3 % reported making an attempt to quit but less than half (45.1 %) were successful. Among women who continued to smoke during pregnancy the majority (55.8 %) reported that they felt unable to quit, and 9.3 % reported that they considered smoking cessation was not an important health issue for them. Participants who continued to smoke during pregnancy were more likely to report fetal (χ2 = 11.41; df = 5;p < 0.05) and newborn complications (χ2 = 6.41; df = 2;p < 0.05), including preterm birth and low birth weight. Participants who reported that their partners were smokers were more likely to smoke throughout their pregnancy (χ2 = 14.62; df = 1;p < 0.001). High rates of second-hand smoke exposure were reported among both smoking and non-smoking women. Pregnant smokers had significantly higher levels of postnatal depressive and anxiety symptomatology, as measured using the EPDS, than non-smokers. Conclusion Our data supports the importance of ensuring that pregnant women, their partners and close relatives are educated on the health risks of active and passive smoking and how these could have an adverse effect to their fetus and infants, as well as the pregnant women themselves.